Study of Size, Shape and Nanoparticle Concentration Effect in Micro-Channel, Pillar and Flat Channel - Debashis Dey, Ass. Prof.; ., . (International Journal of Engineering and Technology, 2018)
In this study,thermal efficiency was calculatedbased on experimental results of micro channels, flat channel and pillars. Here constant heat flux was applied from the bottom of the test section using film heaters where DC (Direct Current) power was supplied to the heaters and a lamp was used for radiation experiments. The flow through channels and pillars were maintained at constant rate using two syringe pumps. There were eight thermocouples for heater and six thermocouple for radiation to measure the temperature continuously using DAQ (Data Acquisition) system at different locations of the test section. Pressure drop between inlet and exit was recorded using calibrated pressure sensor and the reading was fed to the DAQ system. There were different fluids like DI (De-Ionized) water, 0.05%TiO2 (Titanium di-Oxide), 0.1%TiO2 and again water was used for testing. Similar series of tests were carried out with SiO2 (Silica) as well. It has been found that nano-fluid has significant effect (it is termed as the â€œnanofin effectâ€) on effective convective heat transfer as it creates â€œNanofinâ€ on the substrate surface and effectively increase the area for heat transfer. However, after a certain concentration of nano-fluids, the effective area for fluid passage also decreases and thus convective heat transfer decreases. This is why water repeat case gives best result among all four cases on heat transfer.Â